HISTORICAL BACKGROUND OF SHADGUNYA - Sharma, Dipika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ancient Indian thinkers have discussed various topics related to political science in a comprehensive and subtle way. Shadgunya is an ancient Indian concept, which means a collection of six qualities. This concept is found in various philosophies and religions, such as Hinduism, Buddhism, and Jainism. Shadgunya originated in ancient India. At that time, this concept was found in the Vedas and Upanishads. In the Vedas, Shadgunya was known as "Shadripu", which means six enemies (lust, anger, greed, attachment, ego, and envy). In the Upanishads, Shadgunya was known as "Shadvikas", which means six developments (dhyana, prajna, virya, kshaanti, shiil, and santosh).